Describing patterns of mastitis indicators during a clinical mastitis episode - Panchal, Ditsa (SLU/Dept. of Clinical Sciences (until 231231), 2021)
A total of three dairy farms, run on Automatic Milking System (AMS) and having on average 163, 177, and 99 lactating dairy cows respectively, were included in this study. Two of the farms were located in the Netherlands, and one in Canada. The data was retrieved from the database of DeLaval International AB (Tumba, Stockholm). The study aimed to analyze and describe the changes in patterns of mastitis indicators, recorded by sensors, before, during, and after a case of clinical mastitis (CM). In total, 149 cases of CM were identified in the study period, out of which 91 were a first case of CM during a lactation. Fifty-eight of these cases recovered from CM. Recovery was defined based on the somatic cell count (SCC) values being less than 200,000 SCC/ml during the end of the follow-up period. The parameters studied were the SCC, electrical conductivity (EC), and lactate dehydrogenase (LDH) levels of the milk for recovered and non-recovered cases. The statistical analyses were carried out on recovered cases with linear mixed models and results presented as estimated marginal means that were used to analyze the patterns of mastitis indicators for an episode of CM. Further, association analysis was also carried out to check the strength of the relationship between the individual mastitis indicator before and during the treatment initiation and the end of the follow-up period i.e., after 48 days of the treatment initiation. It was found that for recovered cases, the increase in SCC values started approximately 5-8 days before achieving a peak whereas the EC values began to increase relatively later, i.e., approximately 1-4 days before attaining a peak. LDH values, for both, recovered and non-recovered cases started to increase the earliest, that is approximately 9-12 days before attaining a peak value. Furthermore, for recovered cases, it took approximately 20 days for the SCC, EC, and LDH values to stabilize after achieving a peak value. For recovered cases, the SCC and EC values took 20-24 days to drop to the pre-CM level, whereas for LDH it took up to 28 days. No significant associations between the variation in the individual mastitis indicator before CM and the recovery phase were found. Further research with a larger dataset is needed to test whether a pre-treatment variation in SCC, EC, and LDH is of value to predict recovery.